Analisis Pengaruh Pencegahan Korupsi Terhadap Investasi Swasta di Tingkat Kabupaten/Kota di Indonesia (Integritas : Jurnal Antikorupsi, 2022)
: Several previous studies have shown that there are differences in the effect of corruption prevention on private investment. Corruption eradication by the KPK is expected to have a positive and significant effect on investors' decisions when investing in Indonesia. This research studied the long-term effects of corruption prevention on accumulated private investment at the regional level, using cross-sectional data analysis from 507 districts and cities between 2018-2020. The test was conducted using multiple linear regression with the independent variable being the Monitoring Center for Prevention (MCP) as the corruption prevention index. Using White Robust estimator, the study results prove that corruption prevention has long-term positive and significant effects on overall accumulated investment at the district and city levels. The MCP score of a region was greater than other regions for three years, therefore the accumulated investment was greater. These results encourage an increase of urgency when mainstreaming corruption prevention, proving it to be the right choice for investment in Indonesia. To enable local governments to be involved in corruption eradication, the government is expected to provide sustainable local incentive funds (DID).